Pelatihan Strategi Marketing Pelaku Usaha Batik di Desa Jarum pada Masa Pandemi - Tia Restika Aprilia; Fahri Ramadhan; Sadam Ridho Aditya Pratama; Tata Aulia Wardani; Patmisari Patmisari (Universitas Medan Area, 2022)
The purpose of this community service activity which was carried out in Jarum Village, Klaten Regency, Central Java, was to find out how the development of the batik business in Jarum Village, Regency, besides how the marketing strategy was carried out by business actors in Jarum Village, Klaten Regency during the Covid pandemic. 19, the method used is an empirical juridical method with interviews and direct observations to relevant sources and important informants around, after all the data is collected then processed using qualitative descriptive with the aim that all parties understand the contents of the research conducted. . The results of this study confirm that there has been a significant decline in marketing in Jarum village due to lack of knowledge from several parties, therefore socialization related to marketing strategy materials and giving pretest and posttest marketing constraints that are being faced by business actors in needle village is marketing because Therefore, in this case, socialization activities related to the marketing strategy of business actors in the village are important to open up marketing insights in the current era of globalization. This marketing strategy is the basis for determining the planning of a business to develop its production. so as not to be easily displaced by the rigors of product business competition in general.